Deprotometalation–iodolysis and computed CH acidity of 1, 2, 3- and 1, 2, 4-triazoles. Application to the synthesis of resveratrol analogues. Issue 19 (1st October 2015) - Nagaradja, Elisabeth; Bentabed-Ababsa, Ghenia; Scalabrini, Mathieu; Chevallier, Floris; Philippot, Stéphanie; Fontanay, Stéphane; Duval, Raphaël E.; Halauko, Yury S.; Ivashkevich, Oleg A.; Matulis, Vadim E.; Roisnel, Thierry; Mongin, Florence
Graphical abstract: Abstract: 1-Aryl- and 2-aryl-1, 2, 3-triazoles were synthesized by N -arylation of the corresponding azoles using aryl iodides. The deprotometalations of 1-phenyl-1, 2, 3-triazole and -1, 2, 4-triazole were performed using a 2, 2, 6, 6-tetramethylpiperidino-based mixed lithium–zinc combination and occurred at the most acidic site, affording by iodolysis the 5-substituted derivatives. Dideprotonation was noted from 1-(2-thienyl)-1, 2, 4-triazole by increasing the amount of base. From 2-phenyl-1, 2, 3-triazoles, and in particular from 2-(4-trifluoromethoxy)phenyl-1, 2, 3-triazole, reactions at the 4 position of the triazolyl, but also ortho to the triazolyl on the phenyl group, were observed. The results were analyzed with the help of the CH acidities of the substrates, determined in THF solution using the DFT B3LYP method. 4-Iodo-2-phenyl-1, 2, 3-triazole and 4-iodo-2-(2-iodophenyl)-1, 2, 3-triazole were next involved in Suzuki coupling reactions to furnish the corresponding 4-arylated and 4, 2′-diarylated derivatives. When evaluated for biological activities, the latter (which are resveratrol analogues) showed moderate antibacterial activity and promising antiproliferative effect against MDA-MB-231 cell line.